Congenital‐type juvenile xanthogranuloma: A case series and literature review. Issue 5 (12th July 2018) - Oza, Vikash S.; Stringer, Thomas; Campbell, Caren; Hinds, Brian; Chamlin, Sarah L.; Frieden, Ilona J.; Shah, Sonal
Abstract: Background/Objectives: Congenital juvenile xanthogranulomas are infrequently described in the medical literature. We report three previously unpublished cases and systematically review the literature to better characterize this variant. Methods: We surveyed English‐language articles indexed in MEDLINE (1951‐March 2017) and EMBASE (1974‐March 2017) for cases of congenital‐onset juvenile xanthogranulomas confirmed on histopathology. Cases were divided into two categories: cutaneous only or cutaneous with systemic involvement. Results: We identified 31 cases of congenital juvenile xanthogranulomas involving only the skin and 16 cases with systemic involvement. Congenital juvenile xanthogranulomas involving only the skin were large (> 3 cm), presented with various clinical morphologies, and showed signs of regression by 1 year of age. Atypical clinical presentations included exophytic tumors, infiltrative plaques, agminated plaques, and subcutaneous tumors. Complications included ulceration and anetodermic scarring. Infants with congenital cutaneous juvenile xanthogranulomas who also had systemic involvement typically had multiple cutaneous tumors and hepatic involvement and showed signs of spontaneous regression independent of treatment. Conclusions: The medical literature supports that congenital juvenile xanthogranulomas behave in a fashion similar to that of juvenile xanthogranulomas of infancy or childhood. Congenital cutaneous juvenile xanthogranulomas with or without systemic involvement spontaneously regress. The varied clinical presentations in the skin may lead to misdiagnosis, inappropriate examination, and unnecessary treatments. Infants with multiple congenital cutaneous juvenile xanthogranulomas should be evaluated for systemic involvement, with a particular focus on the liver, because 72.2% of these children were found to have hepatic juvenile xanthogranulomas.